Effects of Setup and Material Parameters on the Standard Test for Strand Bond - Polydorou, Thomaida; Riding, Kyle A.; Peterman, Robert J.; Murray, Leigh (My University, 2013)
ASTM recently adopted the Standard Test Method for Evaluating Bond of Seven-Wire Steel Prestressing Strand as ASTM A 1081. The precision and bias statement for this test method has not however been developed. The first step in developing the precision and bias statement is to perform a ruggedness study to determine how the results are affected by allowable variations in methods and materials. A ruggedness study was performed for ASTM A 1081 as the first step in an ongoing interlaboratory study to determent the test method precision and bias. After an initial survey of the pull-out strength of North American Strand in mortar, three strands of differing pull-out strengths were selected for inclusion in the ruggedness study. During this study, the mortar flow, compressive strength at testing, and test loading rate were varied in order to determine their effect on the test results. The results showed that flow was a significant variable in the testing program.
Keywords: Precision; Bias; Standard Test for Strand Bond